Mobile Educational SMSs as Supplementary Means to Teach Sentence Paraphrasing in EMP Course - Arani, Jafar Asgari (International Journal of Interactive Mobile Technologies (iJIM), 2016)
Digital media has been used to enhance language learning for decades. Since the aim of language learning is to develop communicative proficiency, using communication devices and channels that already exist in the classroom is a sensible way of exploiting opportunities for language practice. The ‘anywhere, anytime’ accessibility to educational contents that mobile SMSs, sometimes freely, offer users, means that mobile learning can extend the opportunities for study outside of the classroom. Given the importance of writing, especially for academic purposes in university, the study set a dual goal: firstly, to analyze the outcome of applying supplementary SMS activity to teach English syntax necessary to paraphrase sentences and secondly, to clarify the medical students’ ideas about it. A quasi-experimental, pre-test and post-test, research design was utilized to investigate the hypotheses of this study. Two groups (each 40-second year students of medicine) were randomly assigned to be the experimental and the conventional group. Both groups were taught the same syllabus materials designed for English for Medical Purposes (EMP) II course in a 17-week semester in Kashan University of Medical Sciences, Iran. The former received the SMS –based supplementary contents in a scheduled pattern of delivery two times a week to strengthen their learning while the latter only was taught in a face to face setting. An open questionnaire was used to examine students feedback towards their attitudes. The validity of the questionnaire was examined by giving to a number of professors of English language. The data were also collected and analyzed through an Attitude/ Motivation questionnaire consisting of 12 Likert-scale items, pretest& posttest, paired-samples t-tests, and one way ANOWA. The pretest and posttest data paired t-test likert-scale items analyzed results showed that differences between the experimental and control groups were statistically significant. It was found that the effect of practicing SMS on the students’ English syntax learning was positive. According to the findings, students receiving the supplementary English syntax SMSs noticeably improved their sentence paraphrasing performance and acquired higher grades during the post-test than those in conventional group. Qualitative data from interviews and questionnaires indicate that students hold positive attitudes towards receiving paraphrase syntactic points via SMS. Majority of students in this pilot project considered the educational program offered to be efficient, useful and beneficial. The data gathered revealed mobile syntactic supplementary SMSs can be integrated into EMP II course to enable students to develop better English sentence paraphrasing skills. Mobile SMS; Sentence Paraphrasing; Educational Tool; English for Medical Purposes